Juvenile myelomonocytic leukaemia and Noonan syndrome. Issue 10 (5th August 2014) - Strullu, Marion; Caye, Aurélie; Lachenaud, Julie; Cassinat, Bruno; Gazal, Steven; Fenneteau, Odile; Pouvreau, Nathalie; Pereira, Sabrina; Baumann, Clarisse; Contet, Audrey; Sirvent, Nicolas; Méchinaud, Françoise; et al.
Abstract : Background: Infants with Noonan syndrome (NS) are predisposed to developing juvenile myelomonocytic leukaemia (JMML) or JMML-like myeloproliferative disorders (MPD). Whereas sporadic JMML is known to be aggressive, JMML occurring in patients with NS is often considered as benign and transitory. However, little information is available regarding the occurrence and characteristics of JMML in NS. Methods and results: Within a large prospective cohort of 641 patients with a germline PTPN11 mutation, we identified MPD features in 36 (5.6%) patients, including 20 patients (3%) who fully met the consensus diagnostic criteria for JMML. Sixty percent of the latter (12/20) had severe neonatal manifestations, and 10/20 died in the first month of life. Almost all (11/12) patients with severe neonatal JMML were males. Two females who survived MPD/JMML subsequently developed another malignancy during childhood. Although the risk of developing MPD/JMML could not be fully predicted by the underlying PTPN11 mutation, some germline PTPN11 mutations were preferentially associated with myeloproliferation: 10/48 patients with NS (20.8%) with a mutation in codon Asp61 developed MPD/JMML in infancy. Patients with a p.Thr73Ile mutation also had more chances of developing MPD/JMML but with a milder clinical course. SNP array and whole exome sequencing in paired tumoral and constitutional samples identified no second acquired somatic mutation to explain the occurrence of myeloproliferation. Conclusions: JMML represents the first cause of death in PTPN11 -associated NS. Few patients have been reported so far, suggesting that JMML may sometimes be overlooked due to early death, comorbidities or lack of confirmatory tests.